THE EFFECTIVENESS OF TECHNOLOGY-BASED NON-CLINICAL COMMUNITY INTERVENTIONS TO REDUCE LONELINESS IN THE ELDERLY: A LITERATURE REVIEW - Lestari, Wahyu Agustin Eka (Universitas Airlangga, 2023)
Introduction: The condition of the elderly who experience various declines in biological and psychological functions can affect mobility and social contact, one of which is a sense of loneliness (loneliness). The purpose of this study was to identify the effect of Digital Information Technology-based interventions in reducing loneliness in the elderly. Methods: A systematic review using three electronic databases (Scopus, PubMed, and Web of Science) from the last 7 years (2014-2021). The research used quasi-experiments and Randomized Control Trials (RCT). The data analysis used is descriptive analysis with a narrative approach. Results: There were 8 articles that met the inclusion criteria in the review. All selected studies discuss the effect of Digital Technology-based interventions on reducing loneliness in the elderly. Other interventions are needed such as technological interventions (eg, digital applications (apps), online social networks and social robots) to enhance emotional support and social interaction. Conclusions: This systematic review concluded that the evidence for the effectiveness of technology-based interventions for reducing loneliness in the elderly is uncertain. Basically, technology is not a solution to reduce loneliness in the elderly, but a tool that helps them stay connected with family members, friends, neighbors, etc. and get access to information and resources.